2003
DOI: 10.1046/j.1468-3148.2003.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Organizational Culture: A Comparison of a ‘High’‐ and a ‘Low’‐Performing Residential Unit for People with Intellectual Disabilities

Abstract: Background  This pilot study investigates organizational culture in small community‐based residential services for people with intellectual disabilities, one of the under‐researched determinants of staff behaviour and performance. Staff performance is of primary importance in the provision of quality services. Materials and methods  Two matched residential units were assessed using COMPASS: A Multi‐Perspective Evaluation of Quality in Home Life, and identified as ‘high’ and ‘low’ performing. The organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…Staff performance and behaviour is crucial for quality services for people with ID (Hatton & Emerson 1995). Gillet & Stenfert‐Kroese (2003) found positive organizational culture produced better quality outcomes for residents. It may be that organizational culture associated with more staff and residents interacting in proximity in cluster centres is not conducive to individual development.…”
Section: Discussionmentioning
confidence: 99%
“…Staff performance and behaviour is crucial for quality services for people with ID (Hatton & Emerson 1995). Gillet & Stenfert‐Kroese (2003) found positive organizational culture produced better quality outcomes for residents. It may be that organizational culture associated with more staff and residents interacting in proximity in cluster centres is not conducive to individual development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nature of group home culture and its impact on staff practices have not been well researched, with only a few studies that have used methods such as questionnaires to measure wider organizational culture (Hatton et al . ; Gillett & Stenfert‐Kroese ) and ethnographic accounts of specific aspects of group homes (Croft ; Levinson ). The current authors identified five dimensions of group home culture from a secondary analysis of a large data set from an ethnographic study of five underperforming group homes (Bigby et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies bave used , ©AAIDD DOI: 10,1352DOI: 10, /1934 Standardized measures of cultute drawn from organizational theory to gain insights into tbe actual and ideal cultures in group homes and the organizations that manage them. Gillett and Stenfert-Kroese (2003) used the Organisational Cultural Inventory to identify different cultural styles, and Hatton and colleagues , using a similar measure, identified nine dimensions of organizational cultute, concluding that in most organizations the actual fell short of the ideal. , Studies of this type are useful in understanding links between organizational culture and staff experiences but do not relate closely to resident outcomes or the link between culture and staff care practices.…”
mentioning
confidence: 99%